2014
DOI: 10.1002/2014ja019843
|View full text |Cite
|
Sign up to set email alerts
|

MLT and seasonal dependence of auroral electrojets: IMAGE magnetometer network observations

Abstract: During summer months the maxima occur around 1600-1800 MLT, whereas during winter months the maxima occur around 1800-2000 MLT. Moreover, the summer maxima are much larger than the winter maxima and appear at higher latitudes. The summer maxima are mainly associated with the solar EUV conductivity effect, while the winter maxima are mainly due to the contribution of northward convective electric field. EEJ exhibits a dominant annual variation with maximum in summer and minimum in winter. WEJ also exhibits a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
(60 reference statements)
4
17
0
Order By: Relevance
“…The westward electrojet (as seen by AL) peaks in the post-midnight region, and the eastward electrojet (as seen by AU) peaks in the post-dusk region. This is consistent with observations (Silsbee and Vestine 1942;Allen and Kroehl 1975;Kamide et al 1994;Guo et al 2014). Figure 2 summarizes the field-aligned current (FAC) in the ionosphere (Ebihara and Tanaka 2018).…”
Section: General Overview Of Simulated Substormsupporting
confidence: 88%
“…The westward electrojet (as seen by AL) peaks in the post-midnight region, and the eastward electrojet (as seen by AU) peaks in the post-dusk region. This is consistent with observations (Silsbee and Vestine 1942;Allen and Kroehl 1975;Kamide et al 1994;Guo et al 2014). Figure 2 summarizes the field-aligned current (FAC) in the ionosphere (Ebihara and Tanaka 2018).…”
Section: General Overview Of Simulated Substormsupporting
confidence: 88%
“…In fact the westward electrojet on the dawn side is stronger than the eastward electrojet on the dusk side in that season. Such an imbalance was also reported by Guo et al (2014) for the Northern Hemisphere (see their Fig. 2).…”
Section: Electrojetssupporting
confidence: 81%
“…The westward current had a maximum around 2 MLT, which is where we also observe the equivalent current density maximum as well as the most southward extending equivalent current oval (Figure d). Guo et al [] reported westward electrojet current maxima between 0 MLT and 4 MLT. Viljanen and Tanskanen [] observed the peak of eastward equivalent current around 18 MLT, where we observe the most southward extending equivalent current oval of the eastward equivalent current‐dominated dusk sector.…”
Section: Resultsmentioning
confidence: 99%
“…Viljanen and Tanskanen [2011] also examined the characteristics of the total ionospheric eastward and westward equivalent current in 1994-2010 across the geographic meridian 22.1 ∘ E in the geographic latitude range of 59.0 ∘ -79.4 ∘ N. The westward current had a maximum around 2 MLT, which is where we also observe the equivalent current density maximum as well as the most southward extending equivalent current oval ( Figure 1d). Guo et al [2014a] reported westward electrojet current maxima between 0 MLT and 4 MLT. Viljanen and Tanskanen [2011] observed the peak of eastward equivalent current around 18 MLT, where we observe the most southward extending equivalent current oval of the eastward equivalent current-dominated dusk sector.…”
Section: Equivalent Current Densitymentioning
confidence: 97%